PERAN KADER KESEHATAN DALAM PERAWATAN MASA NIFAS DI PUSKESMAS SIKUMANA KOTA KUPANG TAHUN 2024 - Odi L. Namangdjabar; Ignasensia D. Mirong; Matje Meriaty Huru; Hasri Yulianti; Nurlaelah Al-Tadom; Maria Florentina Nining Kosad; Kamilus Mamoh (Rena Cipta Mandiri, 2025)
The postpartum period is crucial and vulnerable in a mother's life, beginning after delivery and lasting up to six weeks postpartum. During this period, mothers experience physiological and psychological changes that require intensive attention and care to prevent complications. Health cadres play a crucial role in reaching the community, especially postpartum mothers. Cadres are tasked with conducting home visits, providing education, monitoring for danger signs, and referring mothers to health facilities if complaints or complications are found. This role is very strategic in increasing mothers' understanding of the importance of self-care during the postpartum period. This study aims to determine the role of cadres in postpartum care and early detection of complications in postpartum maternal risk cases at the Sikumana Community Health Center in Kupang City. This study used a descriptive design with a cross-sectional approach. The population in this study was 69 Posyandu cadres. Data analysis used univariate analysis with a frequency distribution. The results showed that most Posyandu cadres had sufficient knowledge, strong attitudes, and high motivation regarding postpartum care and early detection of complications.